Impact of Emotional Labour on Burnout - Laxmi (Gyan Management Journal, 2012)
The present study was undertaken with an aim to test the level of emotional labour and bournout -9 the serving staff of a few selected hotels. The paper works at determining the relationship of Emotional labour with the burnout of employees and to study emotional labour and burnout vis-a-vis psycho-demographic factors of the employees. To meet these objectives, one hundred and employees were surveyed using a 22 items Dutch Questionnaire on emotional labour and 14- Maslach Burnout inventory. The results of the study highlighted relatively high positive between emotional labour and burnout. Therefore, it can be concluded that the serving hotels doing Emotional labour are more likely to show signs of burnout. The study has further that emotional labour has significant moderate impact on burnout of employees.